The US-China Trade War Phenomenon (2018-2020) In Economic Diplomacy Perspective - Kholid, Muhammad (Jurnal Politik Indonesia: Indonesian Political Science Review, 2022)
The US-China trade war in 2018-2020 has attracted the attention of many observers and researchers to investigate the driving forces that cause the clash between the two great power countries. Most of them place this phenomenon in the prism of realism by using Thucydides’ trap as a framework. Several studies analyze it within the framework of economics and political economy perspectives. This article tries to fill the gap in the explanation of the US-China trade war by using the economic diplomacy framework. Based on a qualitative method, the author argues that the United States under the leadership of Donald Trump uses tariff bargaining as a diplomatic tool to protect and maintain the supremacy of the United States' innovation and technology against China.